Collective action for public goods provision in low-income groups: a model and evidence from Peru - Almirall, Catherine (2009)
¿Bajo qué circunstancias aparece la acción colectiva? ¿Cuáles son los factores que le dan mayoresposibilidades de éxito? ¿En qué medida las comunidades pobres tienen capacidad para organizarsecon el objetivo de mejorar sus condiciones de vida? Estas preguntas no son nuevas y se hanhecho muchas investigaciones, pero usualmente para el mundo rural. La investigación sobre laacción colectiva en el mundo urbano parece estar más desarrollada en la ciencia política que en laeconomía. La pregunta fundamental se mantiene: ¿cómo se producen y se mantienen los bienespúblicos en comunidades urbanas pobres?Este artículo presenta un conjunto de hipótesis sobre los determinantes de la acción colectiva. La accióncolectiva en barrios urbanos pobres enfrentan tres restricciones básicas: el problema olsoniano,el problema de Maslow y el problema de la exclusión. La parte empírica del artículo utiliza datosrecolectados en barrios marginales de Lima, Perú, en seis tipos de organizaciones comunales. -- Under what circumstances does collective action arise? What contributes to the likelihood that aparticular collective initiative will succeed? To what extent are poor communities capable of organizingthemselves to improve their quality of life? These questions are not new, and economic researchershave studied a number of models in rural settings. Yet the research on collective action in urban areasseems to be more in the political sciences, and an economic model is still lacking. The fundamentalquestion remains: How are public goods produced and maintained by poor urban communities?This paper presents a set of hypotheses on collective action determinants. Collective action in poorneighborhoods faces three key barriers to success: the Olsonian free-rider problem, the Maslowianproblem, and the exclusion problem. The empirical portion of this paper uses data collected inpoor urban and peri-urban areas of Lima, Peru, in six types of community organizations.